Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No.1, 2018, „On Frequency Estimation for Partially Observed System with Small Noises in State and Observation Equations“, pp. 67-72. - Chernoyarov, Oleg V.; Kutoyants, Yury A.; Marcokova, Mariana (Communications - Scientific letters of the University of Zilina, 2018)
Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No.1, 2018, „On Frequency Estimation for Partially Observed System with Small Noises in State and Observation Equations“, pp. 67-72. The third author should have the number 3 at the name, i. e. 3 Mariana Marcokova and two affiliations as follows: 3 Department of Structural Mechanics and Applied Mathematics, University of Zilina, Slovakia and Department of Electronics and Nanoelectronics, National Research University „Moscow Power Engineering Institute“, Russia.